Dipeptidyl peptidase-4 and kidney fibrosis in diabetes. Issue 1 (December 2016) - Shi, Sen; Koya, Daisuke; Kanasaki, Keizo
Abstract Diabetic nephropathy (DN) is the most common cause of end-stage kidney disease worldwide and is associated with increased morbidity and mortality in patients with both type 1 and type 2 diabetes. Recent evidence revealed that dipeptidyl peptidase-4 (DPP-4) inhibitors may exhibit a protective effect against DN. In fact, the kidney is the organ where the DPP-4 activity is the highest level per organ weight. A preclinical analysis revealed that DPP-4 inhibitors also ameliorated kidney fibrosis. In this review, we analyzed recent reports in this field and explore the renoprotective effects and possible mechanism of the DPP-4 inhibitors.